Integrasi Agama dan Sains Melalui Pemaknaan Filosofis Integrated Twin Towers UIN Sunan Ampel Surabaya - Huda, M. Syamsul (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2017)
The article discusses the Integrated Twin Towers paradigm introduced by Sunan Ampel State Islamic University (UIN) Surabaya. The paradigm promulgates an integrated pattern of Islamic studies and sciences as its epistemological basis and philosophical framework. It can be observed within the concept of knowledge development which focuses not only on religious knowledge but also pure scientific knowledge. This paradigm is considered an innovative-solutive scientific idea to bridge interrelated connection of religion and science. The study finds that the idea of the Integrated Twin Towers is epistemologically based on philosophical rationalistic-empirical and religious-normative foundations, which are integrated through Islamic studies and sciences or what so-called Islamic Humanities. The Islamic Humanities is centered upon the integration of Islamic knowledge, social and humanities, science, and technology. The paradigm puts religion and sciences within a harmonious and dialectic gradation point. One tower becomes a subject matter, while other becomes an approach. It also finds that this paradigm methodologically employs interdisciplinary and cross-disciplinary methods or generally called multidisciplinary method.